Evaluation of the Effectiveness of Ship Guiding Services at Tanjung Perak Port Surabaya - Amir, Husnul; Sudirman, Sudirman; Saputra, Toto Dwijaya (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
The efficiency and effectiveness of vessel piloting services at ports play a crucial role in ensuring smooth maritime operations and enhancing maritime safety. This study aims to evaluate the effectiveness of vessel piloting services at Tanjung Perak Port, Surabaya, Indonesia. The evaluation encompasses various aspects of piloting services, including navigational guidance, maneuver assistance, and response to emergency situations. By employing qualitative methodologies, data will be collected from stakeholders, including port authorities, vessel operators, and piloting personnel. Key performance indicators such as response time, safety record, and customer satisfaction will be analyzed to assess the current state of piloting services. Additionally, potential areas for improvement will be identified to enhance the efficiency and effectiveness of vessel piloting services at Tanjung Perak Port. The findings of this study are expected to provide valuable insights for port authorities and stakeholders to optimize piloting services and ensure safe and efficient maritime operations at Tanjung Perak Port, Surabaya.